2011
DOI: 10.3109/0886022x.2011.559680
|View full text |Cite
|
Sign up to set email alerts
|

apoE Expression in Glomerulus and Correlation with Glomerulosclerosis Induced by Adriamycin in Rats

Abstract: Lipid deposition in glomerulus plays an important role in the progression of glomerulosclerosis (GS), and apolipoprotein E (apoE) is an important protein in cholesterol homeostasis. This investigation was performed to explore whether there exists an association between apoE and GS susceptibility. Eighty Wistar rats were randomly divided into two groups: sham operation group and glomerulosclerosis model group, n = 40. The GS disease in rat was induced by uninephrectomy and injecting adriamycin (5 mg/kg) through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…The absorbance was measured using an ultraviolet spectrophotometer, and agarose gel electrophoresis confirmed that there had been no degradation of RNA by visualizing the 18S and 28S RNA bands under ultraviolet light. 40,41 Primers were designed according to primer design principles by Primer Premier 5.0 (Premier Biosoft International, Palo Alto, CA, USA). The primers for PAX2 and internal control β-actin were as follows: F 5 -AAGCGACAGAACCCGACTATGT-3 and R 5 -ACTCCTGTCCCTGCCCCAT-3 for PAX2; F 5 -GCCCCTGAGGAGCACCCTGT-3 and R 5 -ACGCTCGGTCAGGATCTTCA-3 for β-actin.…”
Section: Real-time Reverse Transcription Polymerase Chain Reaction Tomentioning
confidence: 99%
“…The absorbance was measured using an ultraviolet spectrophotometer, and agarose gel electrophoresis confirmed that there had been no degradation of RNA by visualizing the 18S and 28S RNA bands under ultraviolet light. 40,41 Primers were designed according to primer design principles by Primer Premier 5.0 (Premier Biosoft International, Palo Alto, CA, USA). The primers for PAX2 and internal control β-actin were as follows: F 5 -AAGCGACAGAACCCGACTATGT-3 and R 5 -ACTCCTGTCCCTGCCCCAT-3 for PAX2; F 5 -GCCCCTGAGGAGCACCCTGT-3 and R 5 -ACGCTCGGTCAGGATCTTCA-3 for β-actin.…”
Section: Real-time Reverse Transcription Polymerase Chain Reaction Tomentioning
confidence: 99%
“…Ultraviolet spectrophotometer measuring absorbance, agarose gel electrophoresis confirmed that there had been no degradation of RNA by visualizing the 18S and 28S RNA bands under ultraviolet light [17,18]. Primers of were designed according to primer design principles by Primer Premier 5.0.…”
Section: Real Time Reverse Transcription Polymerase Chain Reaction Tomentioning
confidence: 99%
“…Ultraviolet spectrophotometer measuring absorbance, agarose gel electrophoresis confirmed that there had been no degradation of RNA by visualizing the 18S and 28S RNA bands under ultraviolet light. 14,15 Primers were designed according to primer design principles by Primer Premier 5.0. The primers for Smad3 and internal control β-actin were as follows: F 5 0 -CTGGCTACCTGAGTGAAGATG-3 0 and R 5 0 -TGTGAAGCGTGGAATGTCTC-3 0 for Smad3; F 5 0 -GCCCCTGAGGAGCACCCTGT-3 0 and R 5 0 -ACGCTCGGTCAGGATCTTCA-3 0 for β-actin.…”
Section: Real Time Reverse Transcription Polymerase Chain Reaction Tomentioning
confidence: 99%